2015
DOI: 10.3168/jds.2014-8699
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: A pilot study using a mouse mastitis model to study differences between bovine associated coagulase-negative staphylococci

Abstract: Coagulase-negative staphylococci (CNS) are a group of bacteria classified as either minor mastitis pathogens or commensal microbiota. Recent research suggests species-and even strain-related epidemiological and genetic differences within the large CNS group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 42 publications
(41 reference statements)
4
39
0
Order By: Relevance
“…The suspensions rested overnight at −20°C, were centrifuged at 12,250 ×  g for 1 h, and finally the supernatant was centrifuged for another 30 min to obtain a clear pellet. Protein concentration of the lysate samples was determined as previously described (46). Cytokine quantification (ProcartaPlex from eBioscience), LCN2 (Biotechne, USA), and CHI3L1 ELISA (Biotechne, USA) on the mammary gland lysates were all performed according to company guidelines or previously reported (47).…”
Section: Methodsmentioning
confidence: 99%
“…The suspensions rested overnight at −20°C, were centrifuged at 12,250 ×  g for 1 h, and finally the supernatant was centrifuged for another 30 min to obtain a clear pellet. Protein concentration of the lysate samples was determined as previously described (46). Cytokine quantification (ProcartaPlex from eBioscience), LCN2 (Biotechne, USA), and CHI3L1 ELISA (Biotechne, USA) on the mammary gland lysates were all performed according to company guidelines or previously reported (47).…”
Section: Methodsmentioning
confidence: 99%
“…we reported that S. chromogenes originating from a persistent IMI displays a better in vitro bacterial growth in conditions mimicking the mammary gland and in vivo bacterial growth in the mammary glands of mice and dairy cows, compared to S. chromogenes isolated from the teat apex [9,34,35]. Differences in inflammatory response in both mice and dairy cows between strains of the same species and growth inhibition of other major mastitis pathogens have been demonstrated as well [35,36], indicating it is relevant to subtype NAS in future research efforts.…”
Section: Discussionmentioning
confidence: 95%
“…The S. chromogenes TA strain has the ability to inhibit the growth of several major pathogens under laboratory conditions (De Vliegher et al, 2004), whereas the S. chromogenes IM strain does not. The 2 strains also elicit a different immune response in mice (Breyne et al, 2015), and the TA strain is unable to grow in anaerobic iron-depleted medium unlike the IM strain (unpublished data). An inoculum of 1.0 × 10 6 cfu of each strain was prepared to induce an experimental infection.…”
Section: Cns Strainsmentioning
confidence: 94%
“…All heifers were inoculated with 2 different wild strains of Staphylococcus chromogenes and 1 Staphylococcus fleurettii strain. The S. fleurettii isolate was recovered from sawdust bedding in a dairy barn (Piessens et al, 2011;Breyne et al, 2015). The first S. chromogenes strain originated from a cow suffering from a persistent IMI (hereafter referred to as S. chromogenes IM; Supré et al, 2011;Breyne et al, 2015), whereas the second S. chromogenes isolate was cultured from the teat apex of a heifer (hereafter referred to as S. chromogenes TA; De Vliegher et al, 2004;Breyne et al, 2015).…”
Section: Cns Strainsmentioning
confidence: 99%
See 1 more Smart Citation